2018
DOI: 10.1038/s41419-018-0436-x
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrially targeted antioxidant MitoQ protects the intestinal barrier by ameliorating mitochondrial DNA damage via the Nrf2/ARE signaling pathway

Abstract: Disruption of the mucosal barrier following intestinal ischemia reperfusion (I/R) is life threatening in clinical practice. Mitochondrial dysfunction and oxidative stress significantly contribute to the early phase of I/R injury and amplify the inflammatory response. MitoQ is a mitochondrially targeted antioxidant that exerts protective effects following I/R injury. In the present study, we aimed to determine whether and how MitoQ protects intestinal epithelial cells (IECs) from I/R injury. In both in vivo and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(93 citation statements)
references
References 39 publications
4
89
0
Order By: Relevance
“…4 μm of paraffin sections were stained by hematoxylin and eosin (H&E) for light microscopy. Histological score of intestine injury was assessed according to the instructions as previously described [11]. Histological score for every section was evaluated blindly.…”
Section: Histopathological Assessment Of Intestinesmentioning
confidence: 99%
See 3 more Smart Citations
“…4 μm of paraffin sections were stained by hematoxylin and eosin (H&E) for light microscopy. Histological score of intestine injury was assessed according to the instructions as previously described [11]. Histological score for every section was evaluated blindly.…”
Section: Histopathological Assessment Of Intestinesmentioning
confidence: 99%
“…Because of MitoQ's strong antioxidant ability, MitoQ has been suggested to play a protective role in a variety of diseases, including ischemia reperfusion (IR) and liver fibrosis [9,10]. Particularly, Hu et al [11] recently indicated that MitoQ could alleviate the intestinal injury via activating nuclear factor E2-related factor 2 (Nrf2) signaling following IR. Therefore, we hypothesized that MitoQ can protect against the sepsis-induced intestinal injury.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activated Nrf2 signalling shows strong antiapoptotic and antioxidant effects, especially in alleviating intestinal epithelial cell apoptosis during intestinal injury in recent studies. [34][35][36] In the present work, the increased expression of Nrf2 and its downstream factor HO-1 in the Bry-1-treated Il-10 −/− mice may partly explain the protective role of Bry-1 in Il-10 −/− mice.…”
Section: Discussionmentioning
confidence: 50%